Early intravenous immunoglobulin replacement in hypogammaglobulinemic heart transplant recipients: results of a clinical trial. Issue 6 (25th October 2016) - Sarmiento, Elizabeth; Diez, Pablo; Arraya, Mauricio; Jaramillo, Maria; Calahorra, Leticia; Fernandez‐Yañez, Juan; Palomo, Jesus; Sousa, Iago; Hortal, Javier; Barrio, Jose; Alonso, Roberto; Muñoz, Patricia; et al.
Abstract: Background: Immunoglobulin G (IgG) hypogammaglobulinemia (HGG) is a risk factor for development of severe infections after heart transplantation. We performed a clinical trial to preliminarily evaluate the efficacy and safety of early administration of intravenous immunoglobulin (IVIG) for prevention of severe infection in heart recipients with post‐transplant IgG HGG. Methods: Twelve heart recipients with IgG HGG detected in a screening phase of the clinical trial (IgG <500 mg/dL) were recruited. Patients received IVIG (Flebogamma 5%), as follows: 2 doses of 200 mg/kg followed by up to 5 additional doses of 300 mg/kg to maintain IgG >750 mg/dL. IgG and specific antibody titers to distinct microorganisms were tested during follow‐up. The primary outcome measure was development of severe infection during the study period. Data on the primary outcome were matched with those of 13 recipients with post‐transplant HGG who were not included in the clinical trial and with those of 11 recipients who did not develop HGG during the same study period. Results: Mean time to detection of HGG was 15 days. IgG and specific antibody reconstitution (anti‐cytomegalovirus, anti‐ Haemophilus influenza, and anti‐hepatitis B surface antigen antibodies) was observed in IVIG‐treated patients. Severe infection was detected in 3 of 12 (25%) IVIG‐treated recipients, in 10 of 13 (77%) HGG non‐IVIG patients, and in 2 of 11 (18%) non‐HGG patients (log‐rank, 15.31; P =.0005). No severe IVIG‐related side effects were recorded. Conclusion: Data from this study demonstrate that prophylactic IVIG replacement therapy safely modulates HGG and specific antimicrobial antibodies. Our data also preliminarily suggest that IVIG replacement therapy might decrease the incidence of severe infection in heart recipients with HGG.